Effects of sintering temperature on thermoelectric properties of Cu1.8S bulk materials. (27th January 2020) - Gu, Shi-Wei; Zhang, Yi-Xin; Guo, Jun; Feng, Jing; Ge, Zhen-Hua
Abstract: Due to the excellent electrical transmission and potentially excellent thermoelectric (TE) performance, digenite (Cu1.8 S) has attracted more attentions. The combination of mechanical alloying (MA) and spark plasma sintering (SPS) was widely used in preparing Cu1.8 S bulk material, while the TE properties for pure sample were still low. Therefore, it's worth to search a suitable synthesis method to enhance the thermoelectric performance for pristine Cu1.8 S material. In this study, high-density bulk samples of copper sulfide (CS) were fabricated by solid states reaction method combined with SPS at different temperatures. When the SPS temperature was over 873 K, large amounts of sulfur volatilization lead to the appearance of Cu1.96 S second phase and it was considered to have great influence on the thermoelectric performances. The result reveals that the increased sintering temperature could affect the density and grain size of the bulk samples. The highest ZT value of 0.54 was obtained at 773 K for the sample sintered at 773 K, which is also the highest ZT value for the pristine Cu1.8 S in the literature.